2013
DOI: 10.1097/bot.0b013e31826913d6
|View full text |Cite
|
Sign up to set email alerts
|

Does Application Position of the T-POD Affect Stability of Pelvic Fractures?

Abstract: We advocate the placement of pelvic binder devices at the level of the greater trochanters for improved control of the fracture in an unstable pelvic injury. This may result in improved control of hemorrhage, better access to the abdomen, and greater patient comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…One reason for this might be that Sweden is a country with some sparsely populated areas with sometime long distances to larger hospitals. Primary care of high-energy patients is then sometimes conducted at these smaller units, and transport to the definitive level of care happens only after initial physiological stabilization of these patients.It is recommended that a PCCD is applied at the level of greater trochanters [ 4 , 12 , 13 ]. We found that 83 % of the doctors in our study defined the greater trochanters as the level of choice for application of a PCCD.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this might be that Sweden is a country with some sparsely populated areas with sometime long distances to larger hospitals. Primary care of high-energy patients is then sometimes conducted at these smaller units, and transport to the definitive level of care happens only after initial physiological stabilization of these patients.It is recommended that a PCCD is applied at the level of greater trochanters [ 4 , 12 , 13 ]. We found that 83 % of the doctors in our study defined the greater trochanters as the level of choice for application of a PCCD.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors group conducted further analysis comparing the position of T-POD application at the level of the greater trochanters and the anterior superior iliac spine. In this yet another simulated unstable cadaveric fractures, motion analysis demonstrated better stability in sagittal, coronal and axial planes when the T-POD is applied over the greater trochanters as per manufacturers recommendations [ 22 ].…”
Section: Mechanical Effectsmentioning
confidence: 99%
“…2,3 Early pelvic stabilization is postulated to help prevent exsanguination by both decreasing pelvic volume, limiting interfragmentary motion, and thus permitting stable clot formation. [4][5][6][7][8][9][10][11][12][13][14][15] Both commercial binders and traditional sheeting techniques seem to be effective at reducing pelvic volume. [4][5][6][7][8][9][10][11][12][13][14][15] Both commercial binders and traditional sheeting techniques seem to be effective at reducing pelvic volume.…”
Section: Introductionmentioning
confidence: 99%